We, the developing rete testis, efferent ducts, and Wolffian duct, all hereby agree that we need to connect - de Mello Santos, T. [UNESP]; Hinton, B. T. (Wiley, 2019)
Background: The mechanisms by which the rete testis joins the efferent ducts, which joins the Wolffian duct during development, are not known. Mouse and chick models have been helpful in identifying genes that are important for the development of each part, but genes have not been identified as to those that play a role in the joining of each part. Clinical implications of the failure of the male reproductive tract to form a fully functional conduit for spermatozoa are not trivial. Epididymal disjunction, the failure of the efferent ducts to join the testis, is one of several epididymal anomalies that have been observed in some boys who were cryptorchid at birth. Objective: A systematic review of studies focusing on the morphogenesis of the mesonephric duct and mesonephric tubules in different species, and identification of clinical issues should there be failure of these tissues to develop. Design: PubMed and GUDMAP databases, and review of books on kidney development were searched for studies reporting on the mechanisms of morphogenesis of the kidney and epididymis. Main outcomes measure(s): Gaps in our knowledge were identified, and hypotheses coupled with suggestions for future experiments were presented. Results: A total of 64 papers were identified as relevant, of which 53 were original research articles and 11 were book chapters and reviews covering morphogenesis and clinical issues. Investigators utilized multiple species including, human, mouse, chick, Xenopus, bovine, and sheep. Conclusion: Fundamental understanding of the morphogenesis of the male reproductive tract is limited, especially the morphogenesis of the rete testis and efferent ducts. Therefore, it is not surprising that we do not understand how each part unites to form a whole. Only one mechanism of joining of one part of the tract to another was identified: the joining of the Wolffian duct to the cloaca via controlled apoptosis.
Keywords: efferent ducts; epididymis; mesonephric tubules; morphogenesis; rete testis; Wolffian duct